Model for Energy Analysis of Miscanthus Production and Transportation - Alessandro Sopegno; Efthymios Rodias; Dionysis Bochtis; Patrizia Busato; Remigio Berruto; Valter Boero; Claus Sørensen (Energies, 2016)
A computational tool is developed for the estimation of the energy requirements of Miscanthus x giganteus on individual fields that includes a detailed analysis and account of the involved in-field and transport operations. The tool takes into account all the individual involved in-field and transport operations and provides a detailed analysis on the energy requirements of the components that contribute to the energy input. A basic scenario was implemented to demonstrate the capabilities of the tool. Specifically, the variability of the energy requirements as a function of field area and field-storage distance changes was shown. The field-storage distance highly affects the energy requirements resulting in a variation in the efficiency if energy (output/input ratio) from 15.8 up to 23.7 for the targeted cases. Not only the field-distance highly affects the energy requirements but also the biomass transportation system. Based on the presented example, different transportation systems adhering to the same configuration of the production system creates variation in the efficiency of energy (EoE) between 12.9 and 17.5. The presented tool provides individualized results that can be used for the processes of designing or evaluating a specific production system since the outcomes are not based on average norms.